Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/21680396.2021.1919576
|View full text |Cite
|
Sign up to set email alerts
|

Design of nematic liquid crystals to control microscale dynamics

Abstract: Dynamics of small particles, both living such as swimming bacteria and inanimate, such as colloidal spheres, has fascinated scientists for centuries. If one could learn how to control and streamline their chaotic motion, that would open technological opportunities in areas such as the transformation of stored or environmental energy into systematic motion, micro-robotics, and transport of matter at the microscale. This overview presents an approach to command microscale dynamics by replacing an isotropic mediu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 557 publications
1
29
0
Order By: Relevance
“…Experimentally, dissipative solitons were generated in the form of electric current filaments in a 2D planar gas-discharge system [98]. In LCs, different kinds of dissipative solitons have been generated and reported recently [99][100][101][102][103][104][105].…”
Section: Dynamic Dissipative Solitons In Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, dissipative solitons were generated in the form of electric current filaments in a 2D planar gas-discharge system [98]. In LCs, different kinds of dissipative solitons have been generated and reported recently [99][100][101][102][103][104][105].…”
Section: Dynamic Dissipative Solitons In Liquid Crystalsmentioning
confidence: 99%
“…However, the model cannot be used to explain the generation of the directrons observed in (−,−) nematics, in which case both the dielectric and conductivity torques can only stabilize the planar state. Instead, due to the equality of the frequency of the directron oscillation and that of the applied electric field, the main reason of the excitation of the directrons is attributed to the flexoelectric polarization [105]. The study carried out by Aya and Araoka showed that similar directrons can also be generated in nematics of the (−,+) type [101].…”
Section: Dynamic Dissipative Solitons In Liquid Crystalsmentioning
confidence: 99%
“…In these applications, equilibrium structures and their thermodynamic stability at different conditions are concerned. In the recent decade, there is a trend to understand and control transport and dynamics of nematic LCs [10][11][12]. On the one hand, applications of nematic LCs in microfluidics, which require a deep understanding of nematic flows, are in its early stage [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In an isotropic environment, active colloids of both living and inanimate types move along random directions unless their trajectories are biased by gradients of chemicals, temperature, or other cues [5][6][7]. Liquid crystals, used as a medium for active colloids, offer a much higher control level over the microscale dynamics thanks to their longrange orientational order [4,8,9]. In particular, by designing patterns of the nematic director n (n ≡ − n, n2 1) that specifies the preferred direction of molecular orientation [10], one can command the polarity and geometry of propulsion trajectories [11][12][13][14][15][16][17][18], mediate transitions from individual to collective modes of propulsion [17] and control the spatial distribution of microswimmers [14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that a nematic liquid crystal not only directs a microscale motion but could also enable it, as demonstrated by nonlinear electrokinetics [8,11] and by steady directional propulsion of active droplets dispersed in a thermotropic nematic [18]. In the latter case, a spherical water droplet containing randomly swimming bacteria shows directional motility along the overall director [18].…”
Section: Introductionmentioning
confidence: 99%